Health Behaviors and Academic Performance Among Korean Adolescents - Eun Sun So, PhD; Byoung Mo Park, PhD (Elsevier, 2016)
Purpose: This study aimed to examine the most prominent health-related behaviors impacting the academic performance of Korean adolescents. Methods: The 2012 Korea Youth Risk Behavior Web-Based Survey data were analyzed using an ordinal regression analysis after adjusting for general and other health behaviors. Results: Before adjustment, all health behaviors were significantly associated with academic performance. After adjustment for other health behaviors and confounding factors, only smoking [odds ratio (OR) = 2.07, 95% confidence interval (CI) (1.98, 2.16), p < .001], alcohol consumption [OR = 1.22, 95% CI (1.18, 1.27), p < .001], and physical activity [OR = 1.09, 95% CI (1.06, 1.13), p < .001] were associated with lower academic performance, and engaging in a regular diet [OR = 0.65, 95% CI (0.65, 0.62), p < .001] was associated with higher academic performance. Conclusions: Regular diet, reducing smoking and alcohol drinking, and physical activity should be the target when designing health interventions for improving academic performance in Korean adolescents.